Pediatric allogeneic stem cell transplantation from adult SARS-COV-2 positive donor - Shahbaz Memon; Rimaz Mustafa; Mohammed Essa; Mohsen Al Zahrani; Musaed Alharbi; Bader Ahmari; Husam Alsadi (Elsevier, 2023)
Background: Severe acute respiratory syndrome coronavirus 2 (SARS-COV-2) is the cause of COVID-19. Almost 50% of infected people with the virus are asymptomatic. After the introduction of the COVID-19 vaccine, there is a significant reduction in symptomatic infection among vaccinated individuals. The possibility of viral transmission through blood products is unconfirmed yet. Case report: We report a successful hematopoietic stem cell transplant (HSCT) in a patient with sickle cell anemia from an asymptomatic COVID-19-positive donor who underwent stem cell collection under general anesthesia. No complications were encountered during and after the procedure. The marrow was infused safely with good immune reconstitution in the recipient. Conclusion: The report suggests that an asymptomatic COVID-19 positive person might be an acceptable HSCT donor possibly due to existing milder variants of COVID-19.